Advances in Biolinguistics The Human Language Faculty and Its Biological Basis - Fujita, Koji; Boeckx, Cedric (Taylor & Francis, 2016)
Biolinguistics is a highly interdisciplinary field that seeks the rapprochement between linguistics and biology. Linking theoretical linguistics, theoretical biology, genetics, neuroscience and cognitive psychology, this book offers a collection of chapters situating the enterprise conceptually, highlighting both the promises and challenges of the field, and chapters focusing on the challenges and prospects of taking interdisciplinarity seriously. It provides concrete illustrations of some of the cutting-edge research in biolinguistics and piques the interest of undergraduate students looking for a field to major in and inspires graduate students on possible research directions. It is also meant to show to specialists in adjacent fields how a particular strand of theoretical linguistics relates to their concerns, and in so doing, the book intends to foster collaboration across disciplines